Towards a fragility assessment of a concrete column exposed to a real fire – Tisova Fire Test. (1st November 2017) - Rush, David; Lange, David
Highlights: Qualified and quantified damage states for concrete columns and slabs. Vertical temperature distribution during a travelling fire is non-uniform. Application of damage assessment methods to concrete column exposed to real fire. Application of fragility assessment to concrete column using equivalent fire time. Equivalent standard fire durations poorly represent concrete column response. Abstract: Fires can cause substantial damage to structures, both non-structural and structural, with economic losses of almost 1% GDP in developed countries. Whilst design codes allow engineers to design for the primary design driver, property protection is rarely, if ever, designed for. Quantification and design around property protection has been used for some time in the seismic community, particularly the PEER framework and fragility analyses. Fragility concepts have now started to be researched predominantly for steel-composite structures, however, there has been little to no research into the quantification of property protection for concrete structures, whether in design or in post-fire assessments of fire damaged structures. This paper presents selected results from the thermal environment around, and the thermal response of, a concrete column from a large scale structural fire test conducted in Tisova, Czech Republic, inside a four-storey concrete frame building, with concrete and composite deck floors. From the results of the fire test, assessments of the fire intensity are made and used to model the potential thermal profiles within the concrete column and the implications that high temperature might have on the post-fire response of the concrete column. These thermal profiles are then used to assess the reduction of the columns cross-sectional area and are compared to a quantified damage scale for concrete columns exposed to fire. This analyses presented herein will also show that common methods of defining fire intensity through equivalent fire durations do not appropriately account for the complexities of the thermal and structural response of concrete columns exposed to a travelling fire.